Using data taxonomy to achieve security in cloud computing. (22nd July 2019) - Ennajjar, Ibtissam; Tabii, Youness; Benkaddour, Abdelhamid
Cloud computing is a broad concept pertaining to different service models following the utility computing model. Owing to its numerous advantages like high resource elasticity, time improvement, IT maintenance cost reduction, and simplicity, cloud computing paradigm interests many customers. However, notions introduced by the cloud such as the multi-tenancy concept, the computation outsourcing, and the distributed resources increase the security concerns and make trust in cloud providers a critical security challenge. This paper suggests a new method for enhancing the confidentiality of data in the cloud. As data in the cloud has not the same sensitivity, encrypting it with the same algorithms can lead to a lack of security or of resources. The paper proposes to classify data according to a sensitivity level in order to give a suitable security model for each data. By this process, we optimise the use of security mechanisms and the resources consumption.